Potamotrygon limai, sp. nov., a new species of freshwater stingray from the upper Madeira River system, Amazon basin (Chondrichthyes: Potamotrygonidae) - Fontenelle, João Pedro; Da Silva, João Paulo C. B.; de Carvalho, Marcelo R. (Zootaxa, 2014)
Potamotrygon limai, sp. nov., is described from the Jamari River, upper Madeira River system (Amazon basin), state of Rondônia, Brazil. This new species differs from congeners by presenting unique polygonal or concentric patterns formed by small whitish spots better defined over the posterior disc and tail-base regions. Potamotrygon limai, sp. nov., can be further distinguished from congeners in the same basin by other characters in combination, such as two to three rows of midtail spines converging to a single irregular row at level of caudal sting origin, proportions of head, tail and disc, patterns of dermal denticles on rostral, cranial and tail regions, among other features discussed herein. Potamotrygon limai, sp. nov., is most similar to, and occurs sympatrically with, P. scobina, and is distinguished from it by lacking ocellated spots on disc, by its characteristic polygonal pattern on posterior disc, a comparatively much shorter and broader tail, greater intensity of denticles on disc, more midtail spine rows at tail-base, and other features including size at maturity and meristic characters. Potamotrygon limai, sp. nov., is also distinguished from other species of Potamotrygon occurring in the Amazon region, except P. scobina, by presenting three angular cartilages (vs. two or one). This new species was discovered during a detailed taxonomic and morphological revision of the closely related species P. scobina, and highlights the necessity for thorough and all-embracing taxonomic studies, particularly in groups with pronounced endemism and morphological variability.